Study on youth handball regulations: a documental analysis on the mandatory use of individual defensive system in under-12 and under-14 competitions (Journal of Physical Education (Maringá), 2018)
Youth competitions should be transformed into a learning environment appropriate to the development of physical, psychological, technical-tactical skills adjusted to young players. In handball competitions the use of compulsory individual defense from 11 to 14 years of age is presented by literature, but in-depth studies are required. This study describes the use of the individual defensive system in under-12 and under-14 handball competitions, based on chronological-temporal and structural-functional aspects. We conducted a documental research in São Paulo competitions held in 2016, through methodological triangulation between qualitative methods. The use of individual defensive system is mandatory in specific periods of the game, is used with greater volume from 11 to 13 years of age, being used by a minimum proximity of one meter between defenders and attackers and is performed at least in defensive half-court. It is a defensive system that suits the learning of these categories, but demands attention of coaches for the physiological questions of young athletes. The possibility of exploiting larger defensive spaces presupposes the existence of punishments to inhibit gamesmanship and cheating attitudes of coaches and athletes in search of offensive and defensive logic of the game compliance.